Flexible Biphasic Functional Electrical Stimulator for Children with Cerebral Palsy - Zakaria Hussain; Harith Firdaus Mustapha; Emilia Noorsal; Khairul Azman Ahmad; Kriangkrai Sooksood (My University, 2021)
The functional electrical stimulator, FES has been extensively used for rehabilitation, however, in children with cerebral palsy, the need for a suitable FES device is vital. The current available FES device on the market is mostly not a robust and multifunction device. The need of flexible FES where the parameter that can be adjusted is very important to develop In this paper, a biphasic functional electrical stimulator (FES) has been designed and implemented.. The parameter that need to be controlled in a rehabilitation activity for children with cerebral palsy such as voltage, current, frequency and pulse width. The main parts in the design of the simple biphasic functional electrical stimulator are controller, a digital-to-analog converter, and a constant current source. The constant current source consists of a biphasic amplifier, summing amplifier and Howland pump charge circuit. The result show that the Functional Electrical Stimulator developed capable to meet with the performance of the stimulated design in Proteus and capable to achieved the desired output needed for rehabilitation for children with cerebral palsy.
Keywords: Muscle activation and electromyography studies; Cerebral Palsy and Movement Disorders; Conducting polymers and applications